PEDAGOGICAL CONDITIONS FOR THE IMPLEMENTATION OF THE HARMONY OF PHYSICAL AND MENTAL DEVELOPMENT IN STUDENTS (American Journal of Pedagogical and Educational Research, 2025)
The article reveals that in solving problems of applied research in the field of physical culture, the basis for the extensive use of the general educational potential of science, aimed at studying the characteristics of physical and mental development of students.